2018
DOI: 10.1111/odi.12939
|View full text |Cite
|
Sign up to set email alerts
|

Lack of association between LTF gene polymorphisms and different caries status in primary dentition

Abstract: The LTF rs1126477 and rs1126478 polymorphisms showed no association with the different levels of caries risk in our Chinese paediatric cohort.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…The articles had been published from 2008 to 2019. Eleven studies had been conducted on Caucasians [12, 14-16, 18-23, 25], four studies had been conducted on Asians [5,13,17,24], and one on mixed [11] ethnicities. Eleven studies evaluated children [5, 11, 13-16, 18-20, 22, 24], three studies evaluated adults [17,21,23], and two studies evaluated both adults and children [12,25].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The articles had been published from 2008 to 2019. Eleven studies had been conducted on Caucasians [12, 14-16, 18-23, 25], four studies had been conducted on Asians [5,13,17,24], and one on mixed [11] ethnicities. Eleven studies evaluated children [5, 11, 13-16, 18-20, 22, 24], three studies evaluated adults [17,21,23], and two studies evaluated both adults and children [12,25].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Eleven studies evaluated children [5, 11, 13-16, 18-20, 22, 24], three studies evaluated adults [17,21,23], and two studies evaluated both adults and children [12,25]. Four studies had assessed LTF rs1126478 in 1556 cases and 1106 controls [5,16,20,24]. Five studies had assessed ENAM rs1264848 in 934 cases and 600 controls [11,14,19,22,25].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…The articles had been published from 2008 to 2019. Eleven studies had been conducted on Caucasians [12,[14][15][16][17][18][19][20][21][22][23], four studies had been conducted on Asians [5,13,24,25], and one on mixed [11] ethnicities.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Eleven studies evaluated children [5,11,[13][14][15][16][17][18][19]21,25], three studies evaluated adults [20,22,24], and two studies evaluated both adults and children [12,23]. Four studies had assessed LTF rs1126478 in 1556 cases and 1106 controls [5,16,19,25]. Five studies had assessed ENAM rs1264848 in 934 cases and 600 controls [11,14,18,21,23].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Furthermore, host genetics plays a determinant role. Some polymorphisms, such as those found in lactoferrin, a natural antibacterial protein 369 (note: recent research found no association between gene polymorphism and caries in primary teeth 370 ), or in the production of salivary mucins that cover and protect the mucosa and tooth surface, 371 may influence caries susceptibility. If enamel differs in sensitivity to acid, then it may be possible that the microbial challenge required to initiate and propagate caries is not equivalent at all sites.…”
Section: Dental Caries and Cariologymentioning
confidence: 99%